(Great) employees only : - Dauten, Dale A (John Wiley & Sons, 2006)
"A mediocre employee in your group is more than one mediocre employee--he or she is a human multiplier-effect, to the downside. If you have even one mediocre employee, you have announced to the world that mediocrity is okay by you, while conceding that you are willing to slow the entire group for the sake of the worst employee. Thus, allowing that one person to stay is not being kind or generous; it's dangerous. It's dangerous for the individual, who knows that, at some level, he or she is doing second-rate work, and who you are locking into mediocrity, and it is dangerous for the group, which is slowed and distracted." --from (Great) Employees Only